Analisis Semiologi Roland Barthes pada Teks Lirik Lagu Nanatsu no Ko Karya Noguchi Ujo - Akhmad Saifudin; Fajria Noviana (IZUMI, 2023)
Examining literary texts, especially poetry or song lyrics, is generally always related to the problem of meaning. This is a natural thing because poetry is always conveyed in indirect language. Nevertheless, poetry research should understand more than just the meaning of poetry; more critical is how to manage understanding, imagination, and the role of the plurality of texts in uncovering its significance. This research is in line with that. Namely, it aims to examine the significance and appreciation of the lyrical text of a children's song entitled Nanatsu no Ko by Noguchi Ujo. This study uses the text semiology approach or textual narrative analysis proposed by Roland Barthes. The data analysed is the Lexia, the units of reading that comprise the entire text. The lexias have been determined and then analysed using five narrative codes: hermeneutic, proaretic, semic, symbolic, and references codes. This study also uses significance analysis (denotation and connotation) to understand the semic code and connotation of the text. The results of this study found that the significance of the text is a message of criticism about the author's disappointment with Japan's modernisation policy which abandoned the original identity of the Japanese nation. This significance is obtained through the analysis of narrative codes which show the role of plural texts, even though they are conveyed in the form of children's song lyrics, with simple and easy-to-understand diction and arrangement. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor